Informalidade do trabalho e flexibilização das normas laborais - Melo, Mariana Tavares de (2007)
This study has the purpose to promote a brief discussion about the develop process theories of precarization of the labor relations since the First Industrial revolution till the present days. Eventually, after years of social fights and political demands, the labor universe still finds itself fragilized in front of one of the biggest deconstructive threats of the modern neo-liberalism I mean the flexibilization of the Labor Legislation. The economic power of the capitalistic system has intensified itself in the form of the economies globalization, limiting social and economic inclusion opportunities, increasing the number of workers that are excluded from the formal labor market, emphasizing the growth of the informal labor, promoting the maximization of the richness concentration of the international financial institutions and fortifying the performance of the great multinational enterprisers groups. In this sense, the national markets of labor and production have been the main target of the cumulative interests of the global capitalistic politic. Then that appears the deregulation tendency over the Labor Laws in spite of the free collective negotiation between employers and employees and, the intensification of the enterprises profits. Believing that the split of the positive labor rights symbolizes serious losses for the workers in general, this research defends the idea that the flexibilization of the Labor s Law Consolidation is prejudicial for the proletarian category and, in this way, it might not be completely admitted by the Law operators.